Isolated Pediatric Pancreatic Transection Secondary to Ocean-Related Trauma - Kulaylat, Afif N; Pastor, Danielle M; Santos, Mary C (JOP. Journal of the Pancreas, 2013)
Context Isolated pancreatic transection is a rare but well-recognized complication following blunt trauma of the abdomen. Diagnosis at presentation may be difficult and delayed due to subtle initial symptoms and evolving nature of the injury. Case report We describe an isolated complete pancreatic transection in a 14-year-old female secondary to a previously unreported and highly unusual mechanism (being tossed by a wave). Diagnosis was obtained by computed tomography scan 24 hours following initial trauma. She was managed operatively with an open distal pancreatectomy with splenic preservation and no subsequent complications. Conclusions The force sustained from the blunt abdominal trauma of being tossed by a wave can be significant. The management of pancreatic injuries in children, particularly in the context of ductal transection, is controversial. Timely recognition and management is critical to optimal outcomes. Early operative intervention may help to avoid complications such as abscess or pseudocyst formation. Image: CT scan of the abdomen demonstrating complete transection of the pancreas.